2011
DOI: 10.1007/s13191-011-0067-8
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of the Effect of Various Denture Adhesives Available in Market on the Retentive Ability of the Maxillary Denture: An In Vivo Study

Abstract: "Every human being has a divine right to enjoy the health to its fullest." Oral and Dental health is not an exception to this dictum. The speciality of Prosthodontics has emerged as a science to provide replacement of missing dentition for its form and functions along with associated structures. Any successful complete denture treatment combines exemplary technique, effective patient rapport, patient education, and familiarity with all possible management options in order to provide maximum satisfaction to pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 16 publications
2
19
0
5
Order By: Relevance
“…The reason of choice was easy availability, cost effectiveness, biocompatibility, and ease of use. [12][13][14][15][16][17][18]24 Numerous studies have been done to evaluate retention objectively, subjectively or by combination of both, but advantage of objective study is that it is free from influence of patient's perception. Also, in vivo study has an advantage over in vitro study for being clinically more relevant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reason of choice was easy availability, cost effectiveness, biocompatibility, and ease of use. [12][13][14][15][16][17][18]24 Numerous studies have been done to evaluate retention objectively, subjectively or by combination of both, but advantage of objective study is that it is free from influence of patient's perception. Also, in vivo study has an advantage over in vitro study for being clinically more relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Spindle handle mechanism was used to produce dislodging force since it is reported to be the most convenient and more accurate method for producing nearly accurate dislodging forces by Kumar and Thombare. 15 Force was applied at the center of denture as Colón et al concluded in their study that center of the denture (middle portion) was considered the most reliable position for the testing of the retention. 26 In the present study, the retention of well-fitting maxillary denture was evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…revistas relacionado à utilização destes materiais, para que possa aproveitar o máximo de resultados sem agredir a saúde dos tecidos orais (9). Para Valle, Godoy e Garcia, o uso de adesivos oferece segurança aos pacientes, tanto física como psicológica, frente ao deslocamento de suas próteses, favorecendo a mastigação.…”
unclassified